Women Student Motivation in Learning Arabic Language During the Covid-19 Pandemic - Nur Hasnah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This study aims to determine the motivation of female students to learn Arabic in online-based learning in class X PK at MAN Lima Puluh Kota. There have been several types of research related to women's motivation in studying. Women were found to have a higher motivation than men in terms of studying. However, during the Covid-19 pandemic, women's learning motivation decreased. This paper uses mixed methods by using questionnaires and interviews as the research instrument. Based on processed data, female students’ motivation during online learning decreased due to internal and external factors. Many students experience physical complaints of eye fatigue and complaints of difficulty resting due to piling up tasks, and other complaints such as headaches, body aches. The psychological complaints also including having technical problems and difficulty logging in, limited internet quota, and difficulty focusing on studying at home.Penelitian ini bertujuan untuk mengetahui motivasi siswa perempuan belajar bahasa Arab pada pembelajaran berbasis daring di kelas X PK di MAN Lima Puluh Kota karena melalui penelitian yang telah banyak dilakukan, perempuan memiliki motivasi yang tinggi dibandingkan laki-laki dalam belajar. Namun pada masa pandemic covid-19 motivasi belajar perempuan menurun.Metode Penelitian ini menggunakan metode campuran dengan teknikangket dan wawancara.Berdasarkan data yang telah diolah, ditemukan bahwa motivasi siswa perempuanselama pembelajaran daring mengalami penurunan karena faktor internal dan eksternal. Faktor internal yaitu keluhan fisik dan psikis yang dialami oleh siswa, perempuanselama pembelajaran daring. Keluhan fisik yang banyak dialami siswa adalah kelelahan pada mata dan keluhan sulit istirahat karena tugas yang menumpuk serta keluhan lainnya seperti sakit kepala, badan pegal-pegal dan lain-lain. Adapun keluhan psikis yaitu aplikasi yang sering error dan susah login, keterbatasan kuota internet dan kesulitan untuk focus dalam belajar sewaktu di rumah.